Morphological and molecular analysis of the collagen fibers in inflammatory process - De Carvalho, Luis Felipe Das Chagas E Silva [UNESP]; Alves, Mônica Ghislaine Oliveira [UNESP]; Soares, Carlos Alexandre; Almeida, Janete Dias [UNESP]; Da Silva Martinho, Herculano (SPIE, the international society for optics and photonics, 2011)
Collagen makes up one third of the total protein in humans, being formed by the connection of three polypeptide chains arranged in a triple helix. This protein has fundamental importance in the formation of extracellular matrix of connective tissue. This study aimed to analyze the structural changes of collagen, which are resulting from inflammatory processes in oral mucosa, and to make the comparative analysis between the histopathology and the Raman spectra. The samples of tissues with inflammatory fibrous hyperplasia (IFH) and normal mucosa (NM) were evaluated by Raman Spectroscopy, hematoxylin-eosin and Massons trichrome stain. The histological analysis in both stains showed differences in collagen fibers, which was presented as thin fibers and arranged in parallel direction in NM and as collagen fibers are thick, mature and not organized, showing that these types of stain show morphological changes of collagen in IFH. The Raman Spectroscopy discriminate the groups of NM and IFH based on vibrational modes of proline, hydroxiproline and CH3, CH2. The histological stains only shows information from morphological data, and can be complemented by Raman spectra. This technique could demonstrate that inflammatory process caused some changes in collagen structure which is related to aminoacids such as proline and hidroxyproline. © 2011 SPIE-OSA.
Keywords: Collagen; Inflammation; Proline; Raman spectra; Collagen fiber; Collagen structure; Comparative analysis; Connective tissues; Extracellular matrices; Histological analysis; Inflammatory process; Molecular analysis; Morphological changes; Morphological data; Oral mucosa; Polypeptide chain; Structural change; Thin fibers; Total protein; Triple helixes; Vibrational modes; Amino acids; Fibers; Musculoskeletal system; Raman scattering; Raman spectroscopy; Spectrum analysis; Tissue